2022
DOI: 10.3390/atmos13060928
|View full text |Cite
|
Sign up to set email alerts
|

Meteonetwork: An Open Crowdsourced Weather Data System

Abstract: Citizen science has shown great potential for bringing large groups of people closer to science, thanks in part to cooperation with universities and research centers. In this context, amateur weather networks played a major role in the last few decades thanks to a constant growth in technology. An example is given by the Meteonetwork association, born in 2002, and mainly composed by atmospheric science enthusiasts, who built up in time a huge weather station network in Italy. In recent years, they have enlarge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Weather data inside and nearby the three SOL catchments were collected from ARPA Lombardy, and, since spring 2013, meteorological information was also acquired from the MNW association, which has an open‐source database fed by citizen scientists. A comprehensive review about this amateur weather network can be found in Giazzi et al (2022). In Table 1, the total number of stations per variable is shown.…”
Section: Tools and Methodsmentioning
confidence: 99%
“…Weather data inside and nearby the three SOL catchments were collected from ARPA Lombardy, and, since spring 2013, meteorological information was also acquired from the MNW association, which has an open‐source database fed by citizen scientists. A comprehensive review about this amateur weather network can be found in Giazzi et al (2022). In Table 1, the total number of stations per variable is shown.…”
Section: Tools and Methodsmentioning
confidence: 99%
“…When focusing on the ground effects, different weather stations, belonging either to authoritative or citizen science networks can be considered for the Genoa city centre area (Figure 10): 3 stations managed by Arpal (AR-1, AR-2 and AR3), as well as several citizen science stations (CS hereafter) provided by Acronet network (Fedi et al , 2013), Meteonetwork (Giazzi et al , 2022) and Wunderground (Gharesifard et al , 2017) providing a high-density coverage of the historical city center of Genoa (stations CS-0 to CS-5).…”
Section: Rainfall Phenomenamentioning
confidence: 99%
“…The input data from meteorological weather stations comes from two major Italian citizenscience networks, namely Meteonetwork (MNW) and Centro Meteo Lombardo (CML). MNW is a non-profit organization with the task to "promote and disseminate for the benefit of the community the knowledge of meteorological, climatological, environmental, hydrological and glaciological sciences, and their multiple expressions on the territory" (Giazzi et al 2022).…”
Section: Input Datamentioning
confidence: 99%
“…Both citizen-science networks perform a quality check before the data release, in order to avoid missing or anomalous data. These checks include range tests, to exclude values out of the normal range of that particular variable, and cross-validation checks, to exclude anomalous values with respect to the nearby stations (Giazzi et al 2022). In addition, a further check is conducted by the WRF data assimilation (WRFDA) software algorithms, since the absorption of the observations is possible only if the difference between the background model field and the observation value is smaller than a predefined threshold.…”
Section: Input Datamentioning
confidence: 99%
See 1 more Smart Citation